2000
DOI: 10.1086/315686
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mutations Associated with Reduced Antiretroviral Drug Susceptibility among Human Immunodeficiency Virus Type 1 Seroconverters in the United States, 1993–1998

Abstract: To assess the prevalence of mutations associated with decreased antiretroviral drug susceptibility, specimens were tested from persons infected with human immunodeficiency virus (HIV) during 1993-1998. Subjects were drug naive and were attending sexually transmitted disease clinics in 6 US cities. All were enrolled consecutively and had tested negative for HIV during the 2 years before enrollment. Plasma specimens from patients having >/=1 reverse transcriptase (RT) or primary protease mutation were tested phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…However, our overall TDR data mirror the mutation rates reported in other studies within the United States (Castor et al, 2012;Huaman et al, 2011;Hurt et al, 2009;Little et al, 1999;Little et al, 2002;MacVeigh et al, 2013;Readhead et al, 2012;Ross et al, 2007;Truong et al, 2011;Weinstock et al, 2000;Weinstock et al, 2004;Wheeler et al, 2010;Yanik et al, 2012;Youmans et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, our overall TDR data mirror the mutation rates reported in other studies within the United States (Castor et al, 2012;Huaman et al, 2011;Hurt et al, 2009;Little et al, 1999;Little et al, 2002;MacVeigh et al, 2013;Readhead et al, 2012;Ross et al, 2007;Truong et al, 2011;Weinstock et al, 2000;Weinstock et al, 2004;Wheeler et al, 2010;Yanik et al, 2012;Youmans et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our rate of 15% NNRTI mutations contributing to NNRTI resistance was higher than what was typically reported for this drug class (Castor et al, 2012;Huaman et al, 2011;Hurt et al, 2009;Little et al, 2002;MacVeigh et al, 2013;Readhead et al, 2012;Ross et al, 2007;Taniguchi et al, 2012;Truong et al, 2011;Weinstock et al, 2000;Weinstock et al, 2004;Wheeler et al, 2010;Yanik et al, 2012;Youmans et al, 2011). The increase in TDR was primarily due to NNRTI mutations and occurred during the 4-year study period in a trend similar to other studies in the United States (Grant et al, 2002;Ross et al, 2008;Shet et al, 2006;Simon et al, 2002).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Patients who are infected with drug-resistant HIV-1 and initiate antiretroviral therapy show poorer treatment responses than patients who are infected with wild-type (WT) viruses (17,24). A number of studies have shown that the prevalence of viruses with drug resistance mutations in acutely or recently infected persons varies between 10 and 20% (1,3,17,23,24,(34)(35)(36).…”
mentioning
confidence: 99%